Obesity and the Risk for Surgical Site Infection in Abdominal Surgery. Issue 4 (April 2016) - Winfield, Robert D.; Reese, Stacey; Bochicchio, Kelly; Mazuski, John E.; Bochicchio, Grant V.
Obesity is a risk factor for surgical site infection (SSI) after abdominal procedures; however, data characterizing the risk of SSI in obese patients during abdominal procedures are lacking. We hypothesized that obesity is an independent risk factor for SSI across wound classes. We analyzed American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) data for 2011. We calculated body mass index (BMI), classifying patients according to National Institute of Health (NIH) BMI groups. We excluded records in which height/weight was not recorded and patients with BMI less than 18.5. We examined patients undergoing open abdominal procedures, performing univariate and multivariate analyses to assess the relative contribution of obesity to SSI. Study criteria were met by 89, 148 patients. Obese and morbidly obese patients had significantly greater SSI rates in clean and clean-contaminated cases but not contaminated or dirty/infected cases. Logistic regression confirmed obesity and morbid obesity as being independently associated with the overall SSI development, specifically in clean [Obesity odds ratio (OR) = 1.757, morbid obesity OR = 2.544, P < 0.001] and clean-contaminated (obesity OR = 1.239, morbid obesity OR = 1.287, P < 0.001) cases. Obesity is associated with increased risk of SSI overall, specifically in clean and clean-contaminated abdominal procedures; this is independent of diabetes mellitus. Novel techniques are needed to reduce SSI in this high-risk patient population.